Frequency and severity of pain and symptom distress among patients with chronic kidney disease receiving dialysis (Swiss Medical Weekly, 2013)
QUESTION UNDER STUDY: Data on pain management in haemodialysis patients with end-stage renal disease are scanty. Our study aimed to collect information on the frequency and severity of pain and symptom distress among long-term dialysis patients in southern Switzerland. METHODS: Patients with chronic kidney disease stage 5, on dialysis, treated in five nephrology units in southern Switzerland, who had given informed consent and were able to complete the survey, were interviewed to assess pain and correlated symptoms using a Visual Analogue Scale (VAS), the Brief Pain Inventory and the Edmonton Symptom Assessment System. To evaluate the impact of symptoms, the Instrumental Activities of Daily Living questionnaire was used. RESULTS: One hundred and twenty-three patients, aged 36–90 years and with a mean time on dialysis of 3.5 years, were interviewed. Pain was experienced by 81 patients during the 4 weeks before the interview: 68 had chronic pain; 66 reported pain intensity higher than 5 on the VAS; 35 identified musculoskeletal pain as the most disturbing pain. Five patients used drugs to cope with pain during the night. Asthenia and fatigue were prevalent concomitant symptoms. Asthenia, fatigue, sleep disturbances, dyspnoea, loss of appetite, nausea/vomiting and anxiety were correlated with pain. The majority of the patients reported that their pain limited their daily life activities. CONCLUSIONS: Pain severity and symptom distress in dialysis patients are important, but underestimated and undertreated. They interfere with sleep quality and daily living. Routine assessment of pain burden, pain management similar to that used in palliative care, and adequate analgesic use to treat specific dialysis-associated pain syndromes should be considered in guidelines.